Preparation and in vitro/in vivo evaluation of metformin hydrochloride rectal dosage forms for treatment of patients with type II diabetes. (28th May 2017) - Zaghloul, Abdel-Azim; Lila, Ahmad; Abd-Allah, Fathy; Nada, Aly
Abstract: Background: Metformin hydrochloride (MtHCL) is an oral antidiabetic drug and has many other therapeutic benefits. It has poor bioavailability, narrow absorption window and extensive liver metabolism. Moreover, children and elders face difficulty to swallow the commercial oral tablets. Objectives: Preparation, in vitro / in vivo evaluation of MtHCL suppositories for rectal administration to solve some of these problems. Methods: Suppository fatty bases (Witepsol ®, Suppocire ® and Massa ® ; different grades) and PEG bases 1000, 4000 and 6000 (different ratios), were used to prepare rectal suppository formulations each containing 500 mg drug. These were characterized for manufacturing defects, and pharmacotechnical performance and formulations showing superior results were subjected to bioavailability testing in human volunteers compared with the commercial oral tablet (Ref) applying LC–MS/MS developed analytical technique. Results: The preparation method produced suppositories with satisfactory characteristics and free of manufacturing defects. The fatty bases were superior compared with PEG bases regarding the physical characteristics. Three formulations were chosen for bioavailability testing and the results showed comparable bioavailability compared to the Ref. Conclusions: The fatty bases showed superior characteristics compared with the PEG bases. MtHCL formulated in selected fatty bases could be a potential alternative to the commercial oral tablets particularly for pediatric and geriatric patients.